Data Localization and Competitive Reconfiguration: Strategic Adaptation in Emerging Digital Economies - Darsiti (Manexia: Journal of Business, Management, and Creative Economy, 2025)
Data localization has emerged as a defining feature of digital governance in emerging economies, reshaping the institutional environment within which firms compete. While existing research largely frames data localization as a compliance burden or trade barrier, its strategic implications for competitive positioning remain underexplored. This article develops a mechanism-based conceptual framework explaining how data localization induces competitive reconfiguration through four interrelated mechanisms: cost asymmetry creation, reinforcement of territorial embeddedness, architectural modularization, and adaptive capability differentiation. Drawing on institutional theory, international business scholarship, dynamic capabilities, and platform ecosystem research, the study argues that localization policies transform data from a globally scalable resource into a jurisdiction-bound strategic asset. This territorialization alters location advantages, redefines scalability logic from global integration to regional clustering, and differentiates firms based on infrastructural flexibility and adaptive capacity. Competitive outcomes are therefore conditional rather than deterministic: firms with strong domestic embeddedness and high dynamic capabilities are better positioned to convert regulatory segmentation into strategic advantage, whereas centrally integrated and rigid architectures face heightened erosion risks. By reframing data localization as a driver of competitive reordering rather than mere regulatory constraint, the article advances understanding of how institutional boundary-making reshapes digital market dynamics in emerging economies.